IMPLEMENTASI METODE FUN LEARNING DALAM PEMBELAJARAN MEMBACA, MENULIS, DAN BERHITUNG (CALISTUNG) KELAS 1 SD NEGERI 1 CEMPAGA BANGLI - Wulandari, Ida Ayu Gede; Budiadnyana, Anak Agung Ngurah; Wahyuni, Ni Nyoman Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The study is driven by the relevance of mastering reading, writing, arithmetic (calistung) skills in first-grade elementary school students as the main foundation for subsequent learning. In reality, students still experience complications in mastering these skills, necessitating learning methods that can establish a fun also meaningful learning environment. The purpose of this research is to describe how the fun learning approach is used in reading, writing, arithmetic, identify obstacles and efforts made, and analyze the implications of its implementation in first-grade elementary school learners at SD Negeri 1 Cempaga Bangli.  The research utilized a descriptive qualitative technique with first-grade teachers also students as subjects. Techniques for gathering data included recordkeeping, interviews, and observation. Data reduction, data presentation, and conclusion drawing were then used to analyse the data. This outcomes show that the implementation of the fun learning technique in teaching reading, writing, and arithmetic was implemented through different actions including educational games, the use of concrete media, and active interaction between teachers and students. This method was able to increase student engagement, interest, and enthusiasm for learning. Challenges encountered included variations in students' skills, time constraints, the availability of learning media. The efforts made by teachers include providing individual guidance, varying learning methods, and utilizing engaging media. The implications of implementing the fun learning method are seen in increased student engagement in learning and a more conducive and enjoyable classroom atmosphere. Thus, the enjoyable learning approach may be a useful substitute for raising reading levels, writing, and arithmetic learning in early elementary school.